CRIMINAL-LEGAL PROTECTION OF ROBOTICS: NOTION AND CONTENT - Begishev, Ildar R. (International Journal of Law in Changing World, 2022)
Criminal-legal protection of social relations associated with robotics has its specific features based on the following. Introduction of digital technologies, including robotics, into social practice is characterized by exponential growth, which logically entails large-scale and rapid changes in many spheres of social life. This, in turn, requires, on the one hand, prompt, and on the other hand – reasonable reaction taking into account achievements of diverse fields of knowledge: engineering in the broad sense, industry, defense, medicine, etc. Robotic devices are more and more often used when committing crimes. Further, this trend will grow, which will significantly increase the inflicting potential of socially-dangerous infringements and the harm from their commitment. The above said forms the task of counteracting criminal risks determined by robotics introduction and actualizes the issues of elaborating the criminal-legal norms to provide protection of public relations from the infringements complicated by the use of robots. All the above said testifies to the necessity of an objectively formulated and relevant request for elaboration of modern approaches to criminal-legal protection of public relations associated with robotics. It is proposed to interpret such protection as an interconnected system of provisions shaping the criminal-legal policy in the sphere of development, production and application of robots, as well as the liability for socially-dangerous infringements committed with the use of robots and in relation to robots. Such protection includes a complex of measures and ensures security of handling robots, from the moment of their creation till the moment of utilization. The work makes an attempt to elaborate the notion of criminal-legal protection of robotics and to define its content. By their criminal-legal nature, robots can be objects of criminal infringements or means of committing crimes. Robots as material objects having, due to their inherent properties, an increased potential for infringing harm to the public relations protected by law, create a complex of risks and threats which require both actual and prospective measures of counteraction. Effective protection of public relations associated with robotics is insufficient within the existing criminal-legal means. Legal provisions of the criminal law must take into account individual features of robots, causing the need to improve the existing norms and elaborate new provisions of the criminal law. We propose to interpret criminal-legal protection of robotics as an interconnected system of provisions shaping the criminal-legal policy in the sphere of development, production and application of robots, as well as the liability for socially-dangerous infringements committed with the use of robots and in relation to robots.